Markers that can Reflect Asthmatic Activity before and after Reduction of Inhaled Corticosteroids: A Pilot Study. Issue 8 (January 2013) - Kato, Go; Takahashi, Koichiro; Izuhara, Kenji; Komiya, Kazutoshi; Kimura, Shinya; Hayashi, Shinichiro
Evaluation of airway inflammation is important in achieving adequate dosing of inhaled corticosteroids (ICS) for treating bronchial asthma. However, there is no evaluation tool that can be used in clinical settings. We examined biomarkers that can precisely reflect airway inflammation when ICS are decreased in stable asthmatic patients. This was a 12-week, single-arm, open-label clinical study performed at a single university hospital. Twenty-five patients (6 male and 19 female) with stable asthma were included in this study. We investigated whether the levels of nitrite and nitrate in exhaled breath condensate (EBC) increase after ICS reduction. We also investigated whether blood eosinophils, serum immunoglobulin E (IgE), high-sensitivity C reactive protein (hs-CRP), interleukin (IL)-13, IL-17, and periostin are different before and after ICS reduction. Peak expiratory flow (PEF), pulmonary function tests, asthma control test (ACT), and asthma quality of life questionnaire (AQLQ) were also examined. We considered an unscheduled hospital visit due to asthmatic symptoms and decline in average PEF over one week by more than 10% to indicate disease instability, and compared patients with stable and unstable disease for analysis. Unstable status was detected in 5 patients. Age, sex, asthma duration, ACT and AQLQ scores, and the level of serum IgE did not differ between stable and unstable groups. In the unstable group, the total concentration of nitrite and nitrate at the last visit was 9.84 (6.65–11.24) μM. Surprisingly, this was similar to the concentration at the first visit (5.58 (2.94–17.29) μM). Serum periostin before ICS reduction (141.9 [107.7–147.7] pg/mL) was higher in the unstable group than in the stable group (91.5 [78.75–103.5] pg/mL). The unstable group had a higher peripheral blood eosinophil count and wider diurnal variation of PEF at the first visit compared to the stable group. Higher eosinophils in peripheral blood and wider diurnal variation of PEF were predictive markers for unstable disease after ICS reduction. Serum periostin is another candidate for the predictive marker.